A high-performance brain switch based on code-modulated visual evoked potentials - Zheng, Li; Pei, Weihua; Gao, Xiaorong; Zhang, Lijian; Wang, Yijun (Journal of neural engineering, 2022)
Asynchronous brain-computer interfaces (BCIs) are more practical and natural compared to synchronous BCIs. A brain switch is a standard asynchronous BCI, which can automatically detect the specified change of the brain and discriminate between the control state and the idle state. The current brain switches still face challenges on relatively long reaction time ( ) and high false positive rate ( ). In this paper, an online electroencephalography-based brain switch is designed to realize a fast reaction and keep long idle time ( ) without false positives ( s) using code-modulated visual evoked potentials (c-VEPs). Two stimulation paradigms were designed and compared in the experiments: multi-code concatenate modulation (concatenation mode) and single-code periodic modulation (periodic mode). Using a task-related component analysis-based detection algorithm, EEG data can be decoded into a series of code indices. Brain states can be detected by a template matching approach with a sliding window on the output series. The online experiments achieved an average of 1.49 s when the average for each was 68.57 min (1.46 × 10 FP min ) or an average of 1.67 s without This study provides a practical c-VEP based brain switch system with both fast reaction and low FPR during idle state, which can be used in various BCI applications.